Serum levels of advanced glycation end products and their receptors sRAGE and Galectin-3 in chronic pancreatitis - Böhme, Richard; Becker, Carla; Keil, Bettina; Damm, Marko; Rasch, Sebastian; Beer, Sebastian; Schneider, Rick; Kovacs, Peter; Bugert, Peter; Riedel, Jan; Griesmann, Heidi; Ruffert, Claudia; et al. (Pancreatology, 2020)
advanced glycated end products, alcoholic chronic pancreatitis, galectin-3, non-alcoholic chronic pancreatitis, receptor for advanced glycated end products, SNP